Determinación de polimorfismos en los genes de los miR-494, miR-155, miR-144 miR-17, miR-663, miR-4505 y su correlación con trastorno de ansiedad generalizada en una muestra de Bogotá, Colombia - Zamora Gomez, Santiago (Universidad Antonio Nariño, 2022)
The aim of this work was to determine if there is an association between a single nucleotide polymorphism of the genes of miR-494, miR-155, miR-144-3p and miR-17, miR663 and miR-4505, with the diagnosis of generalized anxiety disorder (GAD) in a sample of participants from Bogotá, Colombia. Two groups of participants were classified according to the scores obtained from two scales: the Hospital Anxiety and Depression Survey (HADS), and the Zung Self-Assessment Scale for Anxiety; those who exceeded the cut-off point of the two scales were classified as GAD group and those who scored below the cutoff were classified as control. For the search of the SNPs in proposed miRNA genes, we used databases such as miRNASNP-v3 and PubMed. Reports in the literature provided information about the frequency with which these SNPs occur in the Latin American population. Additionally, we identified genes regulated by the miRNAs with ToppFun and TarBase v.8, and some of the functions. Most SNPs have frequencies less than 0.1, making it impossible to genotype some of them due to the low probability of finding them in the studied population. As an alternative, the rs1452789 (A/T) in the TCF4 gene was genotyped and it was found that this SNP does not present a significant association as a risk factor for GAD.